2011
DOI: 10.1186/1753-2000-5-37
|View full text |Cite
|
Sign up to set email alerts
|

Emotional problems in preadolescents in Norway: the role of gender, ethnic minority status, and home- and school-related hassles

Abstract: Background"The gender gap" refers to a lifelong higher rate of emotional problems in girls, as compared to boys, that appears during adolescence. The gender gap is a well-replicated finding among older adolescents and is assumed to be a cross-cultural phenomenon. However, these cross-cultural studies have not investigated the gender gap in ethnic minorities but sampled ethnic majority adolescents in different countries. Some studies that investigated the gender gap across ethnic groups indirectly (by presentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
0
10
0
1
Order By: Relevance
“…Outcome measures for schizophrenia and other psychoses, ADHD/ODD and autism, were based on ICD-9, ICD-10 and DSM-IV criteria. Four out of five studies on overall mental health found that more non-Western immigrant children reported poorer outcomes than their Scandinavian majority peers [35,36,39,40]. In contrast, Virta et al found that Turkish children in Sweden reported better mental and emotional health than Swedish children and Turkish children in Norway [37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcome measures for schizophrenia and other psychoses, ADHD/ODD and autism, were based on ICD-9, ICD-10 and DSM-IV criteria. Four out of five studies on overall mental health found that more non-Western immigrant children reported poorer outcomes than their Scandinavian majority peers [35,36,39,40]. In contrast, Virta et al found that Turkish children in Sweden reported better mental and emotional health than Swedish children and Turkish children in Norway [37].…”
Section: Resultsmentioning
confidence: 99%
“…In four of the five studies on general mental health outcomes, ethnic inequalities in mental health seemed to disappear after adjusting for SES and other variables [35-37,40]. In the remaining studies on general mental health, schizophrenia and other psychoses, low-functioning autism, and ADHD/ODD, ethnic differences in mental health decreased slightly but remained significant after adjusting for SES and other variables [38,39,41-43].…”
Section: Resultsmentioning
confidence: 99%
“…Other examples of potentially confounding variables are academic factors that have been associated with both emotional problems and parental achievement values, such as school hassles, lack of parental help with homework, and domestic chore burden, which is included as an academic factor as a result of its negative association with academic competence (28). More school hassles have been associated with emotional problems (29). Parental help with homework has been associated with positive academic outcomes (30), although general findings are mixed (31).…”
Section: The Unique Effect Of Parental Achievement Values On Emotionamentioning
confidence: 99%
“…Similarly, participants with two Norwegian-born parents and at least three Norwegian-born grandparents were classified as ethnic Norwegians; they will be referred to as the majority from now on. All preadolescents who were not classified as belonging to the categories "ethnic Norwegian" or "ethnic minority" were excluded from further analyses (9). This yielded a sample of 902 preadolescents who were evenly divided across age and gender.…”
Section: Data Collection and Samplementioning
confidence: 99%